If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 5 = 2(5x + -4) Reorder the terms: 5 + 9x = 2(5x + -4) Reorder the terms: 5 + 9x = 2(-4 + 5x) 5 + 9x = (-4 * 2 + 5x * 2) 5 + 9x = (-8 + 10x) Solving 5 + 9x = -8 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 5 + 9x + -10x = -8 + 10x + -10x Combine like terms: 9x + -10x = -1x 5 + -1x = -8 + 10x + -10x Combine like terms: 10x + -10x = 0 5 + -1x = -8 + 0 5 + -1x = -8 Add '-5' to each side of the equation. 5 + -5 + -1x = -8 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = -8 + -5 -1x = -8 + -5 Combine like terms: -8 + -5 = -13 -1x = -13 Divide each side by '-1'. x = 13 Simplifying x = 13
| 3x+8=-79-9x | | 24+2=-6(8m-4) | | 3-z/8=4 | | 3y-10=47+10/3 | | x^2-0.6=-0.6x | | 2(x+8)=21+2x | | -2(3y-7)=7 | | 9+8.9*3= | | -6(1-4)-3(3-7)= | | 5x-12=9x+8 | | 9z=13-31 | | -8(1+5b)=21 | | 13k-6=9k+2 | | 7.9=d | | 58=27-t | | 9x-7y=-12 | | -8=k/-4 | | 9y-11-5y=26 | | 7x-2y=1 | | 5/9w+8/9=3w | | -22=-6x-22 | | 25+7*3= | | 48/h=-16 | | (4x+40)+3x=180 | | 7q+2=-12 | | w/-31=21 | | 165-4x=23x+24 | | 7y+9y+5y-5= | | 5x+11=2x+17 | | (4x+40)+3x= | | -29=-6+9(a-8) | | 2y-7=-23 |